A resiliência das regiões de Minas Gerais: uma análise com base nas firmas frente ao choque econômico de 2015/2016 - Luana de Castro Lopes (2023)
The widespread sense of economic, political, and environmental uncertainty and insecurity due to globalization has led to an increased perception of the vulnerability of regional economies to various shocks. This situation has driven the search for resilience strategies to respond to the challenges facing countries worldwide. In the last decade, Brazil was affected by an economic crisis highlighting localities' distinct capacities to deal with such pressures. In this dissertation, the objective is to analyze the differentiated effects of the 2015/2016 economic shock on the levels of formal employment in the microregions of Minas Gerais, based on firms, which are the basic units of a regional economy, and the speed of recovery of each one. For this, the indexes of resilience and recovery were calculated for each microregion, and a sample selection model was estimated, considering specific variables of the microregions and the firms. These exercises aim to verify the influence of the analyzed characteristics on the variation of employment during the resistance to the crisis (2014-2016) and during the recovery (2016-2019). The results indicate that the diversity of economic sectors can act as insurance against sectoral declines, contributing to the resilience of the regional economy to external shocks. Productivity proved to be the most impactful characteristic for employment in firms, highlighting the importance of investing and encouraging workers' skills, since this characteristic is directly related to the qualification of the labor force. Finally, this dissertation does not fully cover the extensive research agenda on the characteristics that affect a region's resilience. Thus, there is room for longer-term studies that examine structural issues and consider other ways to analyze resilience, such as reorientation and renewal, as well as the resilience of recovery.